Use of Pineapple (Ananas comosus) as an Immunostimulant in Aquaculture (Review) - Nuri Muahiddah; Wastu Ayu Diamahesa (Jurnal Biologi Tropis, 2023)
The use of pineapple fruit extract as an immunostimulant in aquaculture has become the focus of significant research in efforts to improve the immune systems of aquatic organisms, especially farmed fish. Pineapple fruit extract, which contains bromelain, has attracted attention as a potential natural solution to improve the immune response of fish against pathogens and disease. The main aim of this review is to evaluate the extent to which the use of pineapple as an immunostimulant is effective in improving the immune system of fish or other aquatic organisms in an aquaculture context. This article uses literature study methods from several national, accredited national journals and reputable international journals. Literature study is the process of searching, collecting and analyzing various sources of information relevant to a particular topic. Pineapple extract contains bromelain, which has immunomodulatory and anti-inflammatory properties. It can improve the fish's immune response and reduce inflammation, helping to improve fish health. The use of pineapple fruit extract can reduce dependence on antibiotics in the treatment of sick fish, which is in line with global efforts to overcome antibiotic resistance and environmental impacts. With the right efforts, the use of pineapple fruit extract as an immunostimulant in aquaculture has the potential to increase the productivity and sustainability of the aquaculture industry, as well as reduce dependence on antibiotics and synthetic chemicals. Therefore, further research and development of best practices in the use of pineapple fruit extract in aquaculture are necessary steps to realize its potential as a more environmentally friendly and sustainable alternative.